Pan-European testbed and experimental facility federation – architecture refinement and implementation. (6th July 2010) - Wahle, Sebastian; Harjoc, Bogdan; Campowsky, Konrad; Magedanz, Thomas, Anastasius Gavras
Large future internet research programs such as GENI, FIND, and FIRE are under way that will have a global impact on the current and future internet. Experimental facilities and testbeds are needed to support both revolutionary and evolutionary approaches for re-thinking and improving the internet architecture. The resource federation framework proposed by the authors makes available multi-domain testbeds providing heterogeneous crosslayer infrastructures for broad testing and experimentation purposes. Currently, it is unclear how new concepts and ideas developed by the future internet research community can be integrated into production systems while preserving infrastructure operator investments. Service oriented experimental facilities are required that integrate technologies and concepts across various domains and layers and actively incorporate different market players. In this article, we briefly introduce the network domain federation model as the basis and architectural mindset for the Pan-European Laboratory (Panlab) concept, introduce technical architecture refinements, and outline first implementation results.